2020
DOI: 10.2471/blt.20.255471
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Working condition and health status of 6,317 front line public health workers during the COVID-19 epidemic across 5 provinces in China: a cross-sectional study

Abstract: Background: Public health workers at China CDCs and primary health care institutes (PHI) constitute one of the main workforces for implementing prevention and control measures to contain the COVID-19 epidemic, but their efforts and health status have not been well documented. We aimed to investigate the working conditions and health status of frontline public health workers in China during the epidemic. Methods: Between February 18 to March 1, 2020, we conducted a cross-sectional survey among 2,313 CDC workers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…This could not have been achieved without the immense effort and commitment from medical workers and public health workers. Chinese public health workers, who work at the Chinese Centre for Disease Control and Prevention (China CDC) or primary health care institutes (PHIs), made various contributions to prevent and control the spread of COVID-19, such as epidemiological investigation, surveillance, professional technical guidance, specimen collection and examination, health education and report epidemic data [4,5]. These workers are therefore an indispensable section of the anti-pandemic effort.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…This could not have been achieved without the immense effort and commitment from medical workers and public health workers. Chinese public health workers, who work at the Chinese Centre for Disease Control and Prevention (China CDC) or primary health care institutes (PHIs), made various contributions to prevent and control the spread of COVID-19, such as epidemiological investigation, surveillance, professional technical guidance, specimen collection and examination, health education and report epidemic data [4,5]. These workers are therefore an indispensable section of the anti-pandemic effort.…”
mentioning
confidence: 99%
“…During public health emergencies, such as those resulting from the SARS and MERS epidemics and the COVID-19 pandemic, public health workers and medical workers face numerous stressors such as risk of infection, heavy workload, inadequate equipment and social support [4,6], and are consequently at high risk of developing mental health problems. The mental health and associated risk factors of medical workers have typically been well studied and documented during epidemics such as SARS [7,8] and MERS [9,10], and the ongoing COVID-19 pandemic [11,12].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the Middle East respiratory syndromecoronavirus (MERS-CoV) epidemic has caused elevated stress among healthcare workers [20]. Previously, Li et al indicated that depression and anxiety were observed in 21.3% and 19.0% of the frontline healthcare workers at the beginning of the COVID-19 outbreak [21]. In another study among 1257 healthcare workers, the prevalence of depression, anxiety, insomnia and distress were 0.4%, 44.6%, 34.0% and 71.5%, respectively [22].…”
Section: Discussionmentioning
confidence: 99%